# SOLUTION: please help me out with this thank u Identify the horizontal asymptotes, if any, of the function. f(x)=1/(x-5) x = 0 y = 0 x = -5 y = -5 none

Algebra ->  Algebra  -> Rational-functions -> SOLUTION: please help me out with this thank u Identify the horizontal asymptotes, if any, of the function. f(x)=1/(x-5) x = 0 y = 0 x = -5 y = -5 none       Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Algebra: Rational Functions, analyzing and graphing Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Rational-functions Question 80402: please help me out with this thank u Identify the horizontal asymptotes, if any, of the function. f(x)=1/(x-5) x = 0 y = 0 x = -5 y = -5 none Question 2 Identify the vertical asymptotes, if any, of the function. f(x)=1/(x-5) x = 0 y = 0 x = -5 y = -5 none Question 3 The variable z varies jointly with the product of x and y. Use the given values to find an equation that relates the variables, given x=1, y=1/6, z=3. Question 4 Perform the indicated operation and simplify. (4x^2-4x/x^2+2x-3)/(4x./x^2+x-6) Question 5 Perform the indicated operation and simplify. (4x+1/x^2-4)-(3/x-2) Question 6 Perform the indicated operation and simplify. (5/x+1)+(x-7/x-2) Answer by stanbon(57203)   (Show Source): You can put this solution on YOUR website!Identify the horizontal asymptotes, if any, of the function. f(x)=1/(x-5) ---- As x gets larger and larger f(x) gets closer and closer to 1/x = 0 Horizontal asymptote is y=0 ============ Question 2 Identify the vertical asymptotes, if any, of the function. f(x)=1/(x-5) Vertical asymptote when denominator = 0. Verical asymptote at x=5 ============== Question 3 The variable z varies jointly with the product of x and y. Use the given values to find an equation that relates the variables, given x=1, y=1/6, z=3. z=k(xy) 3 = k(1*1/6) 3 = k(1/6) k=18 y=18(xy) ========== Question 4 Perform the indicated operation and simplify. (4x^2-4x/x^2+2x-3)/(4x./x^2+x-6) [4x(x-1)/(x+3)(x-1)] / [4x/(x+3)(x-2)] Cancel where you can to get: [4x/(x+3)] * [(x+3)(x-2)/4x] Cancel again to get: x-2 ========= Question 5 Perform the indicated operation and simplify. (4x+1/x^2-4)-(3/x-2) lcm = x^2-4 (4x+1)/lcm -3(x+2)/lcm [4x+1-3x-2]/lcm (x-1)/(x^2-4) ============== Question 6 Perform the indicated operation and simplify. (5/x+1)+(x-7/x-2) lcm= (x+1)(x-2) 5(x-2)/lcm + (x-7)(x+1)/lcm [5x-10+x^2-6x-7]/lcm [x^2-x-17]/lcm ========= Cheers, Stan H.